Strategi Pengelolaan SDM dalam Peningkatan Kinerja Perusahaan Berkelanjutan di Era Industri 4.0 - Johan Oscar Ong; Masyhudzulhak Mahazan (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
The industrial growth and technology development need competent human resource in every business organization. The presence of millennial and Generation Z has increasingly dominated workforce presenting a new challenge for organizations to provide work climate that supports their development. It has been surveyed that millennial generation is tech savvy but less patient to stay in an organization. The ability to retain and develop millennial and generation Z is the organization's key success factor to continuously improve its business performance and sustainable growth. The new approach HR management strategies are needed to make sure achieving the business outcome (growth revenue, growth profit, lower cost). The Framework of Organizational Sustainability Model in era 4.0 is designed to map out the HR strategies in order to achieve a sustainable competitive advantage. The organizational key drivers would be the input for this model to support employee core competencies so as to give their outstanding performance and increase productivity. Having skills and experience are not enough for employees, they have to make a commitment and well motivated that is shaped by a strong organizational culture and climate. The current research has provided AMO (Ability, Motivation, Opportunity) model approach to support for the key theoretical propositions. The study is imperative for practitioners and organizations since it offers Human Resource Management strategies as a suggestions and guidelines to develop human capital for improving organizational performance and for gaining sustainable competitive advantage.